The Wordwall Application Improves Junior High School Reading Achievement - Wahyu Taufiq (Academia Open, 2025)
General Background: Reading is a fundamental skill in English language learning and plays a crucial role in developing communicative competence in a global context. Specific Background: Technology-based media, particularly web-based interactive tools such as the Wordwall application, are increasingly integrated into classroom instruction to support engaging learning experiences. Knowledge Gap: Despite the growing use of digital learning platforms, the Wordwall application had not previously been utilized at the research site, leaving uncertainty regarding its role in supporting students’ reading performance. Aims: This study aimed to examine whether the use of the Wordwall application in teaching reading could improve junior high school students’ reading achievement. Results: Using a quantitative experimental approach with pre-test and post-test measures involving 26 students, the findings showed an increase in the mean score from 73.65 before treatment to 85.19 after implementation, supported by paired sample t-test results indicating statistical significance. Novelty: The study provides empirical evidence from a real classroom context where the application had not been previously applied, demonstrating the practical value of interactive web-based tools for reading instruction. Implications: The results suggest that integrating game-based digital platforms into English instruction can support more engaging learning environments and may be considered by teachers seeking alternative strategies to facilitate reading development. Highlights: Post-intervention scores were higher than baseline measurements across participants. Learners showed greater classroom enthusiasm during technology-supported activities. Interactive web tools provided a practical option for assessment and practice. Keywords: Wordwall Application; Reading Achievement; Junior High School; Digital Learning Media; English Instruction